Perancangan Awal Model Sistem Dinamik Pada Sistem Pengendalian Persediaan Material Utama Untuk Distribusi Listrik - Rahmadani, Diajeng Anjarsari; Arvitrida, Niniet Indah (Jurnal Pendidikan Indonesia, 2025)
Inventory management requires coordinated efforts among internal and external stakeholders. The electric power distribution service unit faces challenges in inventory management. Operational constraints including order cycles, fluctuating waiting times, and the absence of buffer stock must be managed while adhering to mandatory service standards, resulting in complexity and uncertainty. The study adopts a dynamic systems approach to identify key stakeholders and map their interdependencies. A causal circle diagram (CLD) is used to visualize and analyze the dynamics of the problem. Then a dynamic system model design was developed to understand the system and find areas for improvement.